2022
DOI: 10.1002/cctc.202200854
|View full text |Cite
|
Sign up to set email alerts
|

Bidentate Rh(I)‐Phosphine Complexes for the C−H Activation of Alkanes: Computational Modelling and Mechanistic Insight

Abstract: The CÀ H activation and subsequent carbonylation mediated by metal complexes, i. e., Rh(I) complexes, has drawn considerable attention in the past. To extend the mechanistic insight from Rh complexes featuring monodentate ligands like P(Me) 3 towards more active bisphosphines (PLP), a computationally derived fully conclusive mechanistic picture of the Rh(I)-catalyzed CÀ H activation and carbonylation is presented here. Depending on the nature of the bisphosphine ligand, the highest lying transition state (TS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
2
5
2
Order By: Relevance
“…This result is in line with the calculations performed by Margl et al [9] . and also with our previous computational study, [6] which demonstrated that the closed‐shell singlet is the predominant ground state in triply coordinated cis ‐Rh(P−P)(Cl) complexes regardless of the specific choice of bidentate phosphine ligands P−P. The following first and second excited states are triplets.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This result is in line with the calculations performed by Margl et al [9] . and also with our previous computational study, [6] which demonstrated that the closed‐shell singlet is the predominant ground state in triply coordinated cis ‐Rh(P−P)(Cl) complexes regardless of the specific choice of bidentate phosphine ligands P−P. The following first and second excited states are triplets.…”
Section: Resultssupporting
confidence: 92%
“…Based on the NEVPT2 results, it is evident that the ground state of cis-Rh(PMe 3 ) 2 (Cl) is a closed-shell singlet species. This result is in line with the calculations performed by Margl et al [9] and also with our previous computational study, [6] which demonstrated that the closed-shell singlet is the predominant ground state in triply coordinated cis-Rh(PÀ P)(Cl) complexes regardless of the specific choice of bidentate phosphine ligands PÀ P. The following first and second excited states are triplets. In the MC(T 2 ) at ~1.4 eV, the electron is excited from the d Rh ð Þ z 2 to the d Rh ð Þ x 2 À y 2 orbital; in MC(T 6 ) at an excitation energy of approximately 1.8 eV, the electron is transferred from the d Rh ð Þ yz orbital to the orbital that is represented by the linear…”
Section: Nevpt2 States Of Trans-rh(pmesupporting
confidence: 92%
See 1 more Smart Citation
“…According to the theoretical and experimental mechanistic studies, [26][27][28] the critical 6https://doi.org/10.26434/chemrxiv-2024-d985s ORCID: https://orcid.org/0009-0006-1302-0571 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0 coordinated intermediate can follow one of two pathways: it could proceed with a subsequent C-C formation step in the carbonylation process or undergo a C-H recombination to regenerate the initial 4-coordinated precursor.…”
Section: Introductionmentioning
confidence: 99%
“…According to the theoretical and experimental mechanistic studies, [29][30][31] the Rh complex undergoes a series of transformations including CO dissociation, C-H activation, CO recombination, C-C coupling and reductive elimination, where C-H activation is identified to be the one of the rate-limiting steps. According to the Bell-Evans-Polanyi principle, the activation energy Δ𝐸 ‡ is highly correlated to the reaction energy.…”
Section: Introductionmentioning
confidence: 99%